A numerical approach to simulate 3D crack propagation in turbine blades. (1st April 2020) - Liu, He; Yang, Xiaoguang; Li, Shaolin; Shi, Duoqi
Highlights: High accuracy meshing strategy is proposed for cracks in turbine blades. A mesh refinement optimum scheme for different types of cracks is presented. The numerical results were validated by the CT specimen's results. Crack propagation of a real turbine blade was numerically investigated. Abstract: To accurately predict three-dimensional (3D) crack propagation in turbine blades, the complex conditions induced by the unique geometry must be considered. In this study, a specific numerical approach to simulate 3D crack propagation in turbine blades was established. First, an appropriate mesh strategy was proposed to accommodate various types of cracks induced in turbine blades, and an optimal scheme of crack mesh refinement was determined. Furthermore, a 3D crack propagation implementation algorithm was employed to consider the crack shape evolution effect. The proposed approach was applied to a high-pressure turbine blade of an aero-engine, and risk levels were evaluated for cracks in different positions. The proposed numerical method is a practical approach that can easily and effectively predict crack propagation behavior in turbine blades. It is expected to contribute toward life management and damage monitoring of turbine blades. Graphical abstract: Image, graphical abstract